Exchange Rate Regime Considerations for Jordan and Lebanon - Bhattacharya, Rina (IMF Working Papers; Working Paper ;, 2003)
This paper addresses the issue of the appropriate exchange rate regimes for Jordan and Lebanon in the context of the literature on optimum currency areas and the arguments concerning the use of the exchange rate as a nominal anchor for the economy. It presents some empirical results on the nature of output shocks in Jordan and Lebanon in the recent past, on the price sensitivity of exports from Jordan, and on currency and asset substitution in both countries. It does not directly address the issue of whether the current exchange rate in either country is overvalued or not, nor does it discuss the issue of an appropriate exit strategy from the current peg.